The Returns to Elite College Education: A Quasi-Experimental Analysis - Massimo Anelli (Center for Economic Studies and ifo Institute (CESifo), 2016)
I take advantage of a sharp discontinuity in the probability of admission to an elite university at the admission score threshold, to estimate causal returns to college education quality. I use a newly constructed dataset, which combines individual administrative records about high school, college admission, college attendance and tax returns. Students with score just above the admission threshold have 52% higher yearly income with respect to just-below-threshold students. This premium is equivalent to a jump from the 44th percentile to the 74th percentile of the income distribution. The richness of the data allows me to explore the counterfactual college career of not admitted students and the potential mechanisms underlying the estimated income premium. I find that students with a just-above-threshold score are less likely to be college dropouts, take six fewer months to graduate, choose different majors and are more likely to have income in the top quartile of the distribution. Cumulated over fifteen years, the time span of income data for my sample, the net premium of attending the elite university amounts to around 120,000.
Keywords: I21; I22; I23; I28; J24; J31; 330; education quality; returns to education; human capital